First simplify the given equation:
color(white)("XXX")y=color(orange)(-3x^2-2x-1)+color(brown)((2x-1)^2)
color(white)("XXX")y=color(orange)(-3x^2-2x-1)+color(brown)(4x^2-4x+1)
color(white)("XXX")y=x^2-6x
One of the easiest ways of finding the vertex is to convert the equation into "vertex form":
color(white)("XXX")y=color(green)(m)(x-color(red)(a))^2+color(blue)(b) with vertex at (color(red)(a),color(blue)(b))
by "completing the square"
(Note that in this case we can ignore color(green)(m) or write it with its implied value of color(green)(1)).
color(white)("XXXXXX")Remember (x+k)^2 = x^2+2kx+k^2
color(white)("XXXXXX")So in this case k=-3
color(white)("XXXXXX") and we will need to add (-3)^2 to complete the square
color(white)("XXX")y=x^2-6xcolor(purple)(+9-9)
color(white)("XXX")y=(x-color(red)(3))^2+color(blue)("("-9")")
which is in vertex form with the vertex at (color(red)(3),color(blue)("("-9")"))
Here is a graph of the original equation to help verify our result:
graph{-3x^2-2x-1+(2x-1)^2 [-7.46, 12.54, -10.88, -0.88]}